أثر تغيرات عرض النقود على الأداء الإقتصادي - علي صاري (جامعة البليدة2-كلية العلوم الإقتصادية والعلوم التجاريةوعلوم التسيير, 2015)
الملخص: تناولنا في مضمون هذه الدراسة موضوع "أثر تغيرات عرض النقود على الأداء الاقتصادي" من الناحية النظرية، وقمنا بإسقاط الجوانب النظرية المدروسة على حالة الاقتصاد الجزائري في الجزء التطبيقي منها. وجاء ذلك كمحاولة للإجابة عن الإشكالية المطروحة في البحث والتي كانت على النحو التالي: "ما هي مجالات تأثير تغير عرض النقود على متغيرات النشاط الاقتصادي الكلي بصفة عامة، وعلى الاقتصاد الوطني بصفة خاصة؟" وقد شملت الدراسة الفترة الممتدة من سنة 1991 (أي بعد سنة من إصلاحات 1990 وبداية ظهور نتائجها) إلى غاية سنة 2014، والتي تمثل نهاية البرنامج الخماسي الثالث (2009 - 2014). وكان الهدف من ذلك هو محاولة لفت الانتباه إلى أهمية دراسة العرض النقدي كمتغير كمي في الاقتصاد، وضرورة تحديد كميته المثلى ومراقبة اتجاه تغيراته، والعمل على جعل كمية النقود المعروضة متلائمة مع الإمكانيات الحقيقية للنشاط الاقتصادي، وبما يحقق التوازن النقدي والحقيقي. هذا وقد تناول الموضوع من خلال عدة عناصر أساسية أهمها: العرض النقدي ومصادر تغيراته. العناصر الأساسية للأداء الاقتصادي. أثر تغيرات عرض النقود على الأداء الاقتصادي. فعالية البنك المركزي في إدارة وتنظيم عرض النقود. أما الجانب التطبيقي، فقد حللنا من خلاله أثر تغيرات عرض النقود على واقع الأداء الاقتصادي الجزائري في الفترة الممتدة من سنة 1991 إلى غاية سنة 2014. حيث أثبتت الدراسة القياسية تلك الآثار المترتبة عن تغيرات عرض النقود على بعض متغيرات النشاط الاقتصادي الوطني، والمتمثلة أساساً في: الناتج المحلي الإجمالي، المستوى العام للأسعار، أسعار الفائدة والصرف، توازن الميزان التجاري وميزان المدفوعات، بالإضافة إلى البطالة والمستوى العام للتشغيل. ويعود ذلك إلى أن عرض النقود يعد من أهم الأدوات التي تستعملها السلطات النقدية في تحقيق الاستقرار الاقتصادي. وخلصنا في الأخير إلى ضرورة تحديد ومراقبة تغير العرض النقدي بما يتوافق واحتياجات النشاط الاقتصادي، إضافة إلى تهيئة الظروف المساعدة على الحد من نمو العرض النقدي، من خلال منح البنك المركزي سلطة الرقابة والإشراف الكاملة على أعمال البنوك، واستعمال الآليات المختلفة في ضبط السيولة النقدية، والعمل على تقليل ربط زيادة عرض النقود بزيادة الاحتياطات الأجنبية، والحد من الإصدار النقدي غير المغطى.Abstract: We dealt with in the context of this study, the subject of the impact of changes in the money supply on the theory of economic performance, and we have to drop the aspects of the theory studied the case of the Algerian economy in the application of them, and try to answer the problem posed in the research, which was as follows: "What are the areas of the effect of changing the money supply on economic activity variables college in general, and on the national economy in particular? " After years of reforms in 1990 and the onset of the results, to the year 2014, which marks the end of the Third Five-Year Program (2009-2014); the goal is to try to draw attention to the importance of the study of the money supply as a variable entirely in the economy, and the need to quantify the optimal and control the direction of its changes, and work to make the amount of money offered compatible with the real possibilities of economic activity and to achieve monetary and real balance. This has been dealt with the issue through several key elements, including: the money supply and the sources of its changes; the basic elements of economic performance; the impact of changes in the money supply on economic performance; the effectiveness of the central bank in managing and regulating the money supply; the side Applied him was analyzed through the impact of changes in display money on the reality of the Algerian economic performance in the period from the year 1991 until the year 2014. Where proven standard study these effects of changes in the money supply to some of the national economic activity variables, mainly of GDP, the general level of prices, interest rates and exchange rates, the balance of the balance of trade and balance of payments, unemployment and the general level of operation; because the money supply is the most important tools used by the monetary authorities in achieving economic stability; and concluded in the fourth to the need to identify and monitor the change in money supply in line with the needs of economic activity, in addition to creating the conditions helping to reduce money supply growth, by giving the central bank oversight authority and supervision of banks and the use of business different mechanisms in cash set, and work to reduce the link to increase the money supply to increase foreign reserves and the reduction of the cash version.
دراسة حالة الجزائر
Keywords: الأداء الاقتصادي.; البنك المركزي; إدارة وتنظيم عرض النقود; الأداء الاقتصادي الجزائري; السيولة النقدية; الإصدار النقدي; الميزان التجاري